Increased prevalence and incidence of anemia among adults in transforming rural China: two cross-sectional surveys. (December 2015) - Wang, Xuecai; Wu, Zhaofan; Chen, Yue; Zhu, Jianfu; Dong, Xiaolian; Fu, Chaowei; Jiang, Qingwu
Abstract Background Anemia remains one of the serious nutrition-related diseases in China, but data on incidence of anemia were less available, especially in rural area which are experiencing rapid urbanization. Out study aimed to estimate both the prevalence and incidence of anemia in transforming rural China. Methods We conducted a combined study of rural adults 18–64 years of age with a repeated cross-sectional component (4456 in 2006 and 2184 in 2008) and a cohort component (1424) in rural Deqing, China. Anemia was diagnosed based on blood hemoglobin levels using the hemiglobincyanide (HiCN) method according to both the World Health Organization (WHO) and Chinese criteria. The prevalence and incidence of anemia and their 95 % confidential intervals (95 % CI) were calculated. Results The prevalence of anemia based on the WHO criteria was 51.5 % in 2006 and 53.7 % in 2008, and the 2-year cumulative incidence was 42.1 %. Of the cases, over 95 % had mild anemia. The prevalence was much lower when the Chinese criteria was used. Both the prevalence and incidence were higher in women than in men and significantly increased with age in men. In both sexes, the incidence sharply increased after 45 years of age. Conclusion Our study showed a high prevalence and incidence of anemia among adults in rural Deqing, China. Monitoring and intervention were needed urgently, especially among individuals over 45 years of age.